INDUCTION OF C-MYC G-QUADRUPLEX DNA AND CYTOTOXICITY OF A CALIX[4]ARENE-CONTAINING BINUCLEAR RUTHENIUM(II) COMPLEX - Ya-Xuan Mi; Shuang Wang; Shuang-Mei Yan; Yue Cui; Ming-He Wang; Ze-bao Zheng; Xiao-Long Zhao (Journal of the Chilean Chemical Society, 2019)
Herein, a binuclear ruthenium(II) complex modified by calix[4]arene group has been prepared. The complex as potential inducer and stabilizer of c-myc G-quadruplex DNA and antitumor reagent were studied. Observations revealed that the complex could bind to c-myc Pu27 and Pu22 DNA strongly with constants of 1.18 × 107 (Pu27) and 4.13 × 106 M-1 (Pu22) via groove mode as determined from absorption and luminescence titrations, as well as CD spectra. Results of continuous variation analysis confirmed that the complex interacted with c-myc G-quadruplex DNA through a 1:1 binding stoichiometry. As verified by PCR-stop assay, the replication of c-myc DNA was effectively blocked by the complex with the complete inhibition at the complex concentration of 4.0 μM both for Pu27 and Pu22, suggesting that the complex could efficiently induce the formation of c-myc G-quadruplex DNA. The appearance of blue TMB solution in the visual experiment also proved that the sequences of Pu27 and Pu22 could fold into G-quadruplex under the induction of the complex. Nevertheless, the complex was found to exhibit weak stabilization ability on c-myc G-quadruplex DNA according to FRET assay, which increased the melting point of c-myc DNA only 3-3.5 °C. The experiments on Topoisomerase inhibition and cytotoxicity of the complex showed that it acted as an inhibitor of TopoI and exhibited moderate anticancer activity against MCF-7 and Huh-7 tumor cells.